Prevalence and associated factors of steroid induced impaired glucose metabolism in obstructive lung diseases, Jimma, and Southwest Ethiopia, Africa - Tadesse, Jarso; Vata, Prabhanjan Kumar; Abebe, Reta Kassa (International Journal of Advances in Medicine, 2016)
Background: Impaired glucose metabolism is one of the complications of steroid therapy in patients with Obstructive lung diseases. Steroid induced impaired glucose metabolism is a serious, but often overlooked, metabolic disorder; it is largely remains under diagnosed. Although this has been reported from western countries, there is no study that evaluated the prevalence of impaired glucose metabolism and its associated factors in Ethiopia in general and in the study area in particular. Aim of the study was to determine the prevalence and associated factors of steroid induced impaired glucose metabolism in Obstructive lung diseases at Jimma University Specialized Hospital chest clinic from November 2014 to July 2015. Methods: A hospital based cross-sectional study design was conducted. In this specific study Convenience sampling used. Data was collected through patient interview and chart review. Serum random glucose was determined during Hospital visit. Descriptive statistics and bivariatelogistic regression analysis were done. A P-vale of <0.05 was considered statistically significant. Results: The study comprised of 90 patients with Asthma and COPD taking systemic steroids visited chest clinic during the study period were included in the analysis. 11.1% of the study subjects had impaired glucose metabolism. The level of RBS level was not associated with any of the independent variables studied (Age and sex of the patient, waist circumference, family history of DM and dose and duration of systemic steroid). Conclusions: This study found that the prevalence of impaired glucose metabolism in obstructive lung diseases on systemic steroids is significant independent of the effect of dose and duration of steroids.